1979
DOI: 10.1037/0022-006x.47.3.509
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathy and violent crime.

Abstract: The relations between psychopathy, violence, and impulsiveness of criminal behavior were examined within a white prisoner sample using level of intelligence as a moderator variable. Unlike most prior research, psychopathy was found to be predictive of violence, but only for less intelligent criminals; about 90% of this group had committed a violent crime compared to 58% for the remainder of the sample. Similarity, the psychopaths with limited intelligence evidenced the greatest impulsivity in the commission of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
2

Year Published

1982
1982
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 33 publications
(40 reference statements)
5
37
2
Order By: Relevance
“…The results of this study are relatively consistent with, although they are not entirely similar to, previous findings (Blakely et al, 1974;Cornell et al, 1987;Hanson, Henggeler, Haefele, & Rodick, 1984;Heilbrun, 1979;Henggeler et al, 1985) In general, however, our results point to the need for a comprehensive model of psychological and sociological variables to explain violent and nonviolent adolescent criminal behavior.…”
Section: Discussionsupporting
confidence: 89%
“…The results of this study are relatively consistent with, although they are not entirely similar to, previous findings (Blakely et al, 1974;Cornell et al, 1987;Hanson, Henggeler, Haefele, & Rodick, 1984;Heilbrun, 1979;Henggeler et al, 1985) In general, however, our results point to the need for a comprehensive model of psychological and sociological variables to explain violent and nonviolent adolescent criminal behavior.…”
Section: Discussionsupporting
confidence: 89%
“…Despite this, the considerable heterogeneity in effect sizes found in these meta-analytic studies raises some concerns about the aggregation of diverse effect sizes across studies. Furthermore, it suggests that there may be sample characteristics (e.g., age, racial, intelligence, socioeconomic status, or cultural background; Heilbrun, 1979;Kosson et al, 1990;Walsh and Kosson, 2007) In line with this suggestion, a prospective study of 199 U.S. offenders found that for European Americans, psychopathy predicted recidivism at lower levels of socioeconomic status (SES) but was unrelated at higher levels of SES. However, for African Americans the predictive power of psychopathy was relatively stable across SES (Walsh and Kosson, 2007).…”
Section: Recidivism and Psychopathymentioning
confidence: 79%
“…IQ has been proposed to moderate the effect of psychopathy on violence such that low IQ psychopaths present greater risk for violence than do high IQ psychopaths and high and low IQ nonpsychopaths (Heilbrun 1979(Heilbrun , 1982(Heilbrun , 1990. Conversely, there is also evidence that IQ and psychopathy combine to predict violence in an additive, rather than a multiplicative manner (Holland, Beckett, and Levi, 1981).…”
Section: Iqmentioning
confidence: 93%